2006
DOI: 10.1080/10550490500419029
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions between Opioids and Antiretroviral Medications: Interaction between Methadone, LAAM, and Delavirdine

Abstract: Understanding the drug interactions between antiretrovirals and opioid therapies may decrease toxicities and enhance adherence with improved HIV outcomes in opioid-dependent individuals. The authors report the results of a clinical pharmacology study designed to determine whether significant pharmacokinetic and/or pharmacodynamic interactions occur between the non-nucleoside reverse transcriptase inhibitor, delavirdine (DLV), and either methadone or levo-alpha acetyl methadol (LAAM) (n = 40). DLV significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The general design of this study has been reported elsewhere [9,10]. Thirty-five individuals participated, including 10 opioid-dependent individuals who had been stable for at least 2 weeks while receiving a daily dose of sublingual buprenorphine/ naloxone of between 16/4 and 20/5 mg and who participated in a 24-h blood and urine sampling study to determine buprenorphine pharmacokinetics followed by administration of either EFV (600 mg daily) for 15 days or DLV (600 mg twice daily) for 7 days, as well as a second 24-h pharmacokinetic study in which blood and urine sampling for buprenorphine and antiretroviral plasma concentrations was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general design of this study has been reported elsewhere [9,10]. Thirty-five individuals participated, including 10 opioid-dependent individuals who had been stable for at least 2 weeks while receiving a daily dose of sublingual buprenorphine/ naloxone of between 16/4 and 20/5 mg and who participated in a 24-h blood and urine sampling study to determine buprenorphine pharmacokinetics followed by administration of either EFV (600 mg daily) for 15 days or DLV (600 mg twice daily) for 7 days, as well as a second 24-h pharmacokinetic study in which blood and urine sampling for buprenorphine and antiretroviral plasma concentrations was performed.…”
Section: Methodsmentioning
confidence: 99%
“…This class of antiretrovirals has previously been shown to have important pharmacokinetic interactions with methadone. Among these, efavirenz (EFV), the most frequently prescribed medication in the class, is a potent inducer of CYP3A4 that has been shown to precipitate opiate withdrawal when administered with methadone [1], whereas delavirdine (DLV) is a known inhibitor of CYP3A4 that increases concentrations of methadone [9]. The goals of the present study included the following: (1) to determine whether the pharmacokinetics of the opioid dependence medication buprenorphine (administered in this study as the buprenorphine/naloxone combination tablet that is used in the clinical setting for the treatment of opioid dependence) are affected by coadministration of either of the NNRTI medications EFV or DLV; (2) to determine whether the pharmacokinetics of these NNRTIs are affected by coadministration of buprenorphine; and (3) to determine whether clinically significant pharmacodynamic effects or toxicities occur when buprenorphine is administered simultaneously with either NNRTI.…”
mentioning
confidence: 99%
“…Methadone has a long half-life and it is unclear if prolonged co-administration of delavirdine and methadone would result in larger increases in AUC and the development of clinical symptoms; therefore, the co-administration of these medications should be undertaken judiciously and with close oversight [149]. A separate study demonstrated that methadone does not significantly effect delavirdine’s pharmacokinetics [150].…”
Section: Interactions Between Methadone and Specific Antiretroviral Mmentioning
confidence: 99%
“…[43][44][45] Regarding adverse events, only a minor effect on corrected QT (QTc) interval duration has been reported with therapeutic doses of buprenorphine-naloxone, without proarrhythmic effects. 46,47 Conversely, methadone can increase the risk of a rare but fatal ventricular arrhythmia (torsades de pointes) because of its substantial QT-prolonging effects, especially at higher doses.…”
Section: Disadvantagesmentioning
confidence: 99%